Relationship between resolution of non‐alcoholic steatohepatitis and changes in lipoprotein sub‐fractions: a post‐hoc analysis of the PIVENS trial. Issue 9 (10th March 2019) - Corey, Kathleen E.; Wilson, Laura A.; Altinbas, Akif; Yates, Katherine P.; Kleiner, David E.; Chung, Raymond T.; Krauss, Ronald M.; Chalasani, Naga; ,
Summary: Background: Dyslipidaemia is frequent in non‐alcoholic steatohepatitis (NASH); however, it is unclear if improvement in liver histology is associated with favourable changes in cardiovascular disease (CVD) risk. Aims: To evaluate the relationship of NASH resolution and lipoprotein subfraction levels, markers of endothelial dysfunction, and macrophage activation. Methods: One hundred and seventeen individuals with NASH who participated in the Pioglitazone vs Vitamin E vs Placebo for the Treatment of Nondiabetic Patients with NASH (PIVENS) trial with paired liver biopsies and serum samples available at baseline and after 96 weeks of treatment were included. Participants in the PIVENS trials received vitamin E, pioglitazone, or placebo for 96 weeks. Lipoprotein subfraction levels, intracellular adhesion molecule 1 (ICAM‐1), vascular cellular adhesion molecule 1 (VCAM‐1), E‐selectin, and sCD163 levels were assessed at baseline and week 96 and their relationship with NASH resolution was examined. Results: Fifty‐seven individuals had NASH resolution and 60 individuals did not have resolution of NASH. NASH resolution was associated with favourable changes in lipoprotein subfraction levels compared to those without NASH resolution. Individuals with resolution of NASH had a significantly increased mean peak LDL diameter (ratio of geometric means [96 weeks vs baseline] 1.007 vs 0.996, P  = 0.004), and higher frequency of LDL phenotype A (58% vs 33%, P  = 0.003) at week 96, after adjustment for relevant co‐variates including treatment group. No differences in VCAM, ICAM, E‐selectin, or sCD163 levels by NASH resolution were found. Conclusions: NASH resolution is associated with favourable changes in a subset of serum lipoprotein levels. More studies are warranted to understand if these favourable changes are associated with decreased risk of CVD.